The Effect of Technology Innovation on Corporate Sustainability in Chinese Renewable Energy Companies - Wang, Pei; Zhang, Zijin; Zeng, Yeli; Yang, Shucheng; Tang, Xu (Frontiers in Energy Research, 2021)
Technology innovation has become the main driving force of China’s economic growth. Sustainable development highlights the harmonious symbiosis of the economy and the ecological environment. Renewable energy companies characterized by technology-intensive and environmental friendliness are playing an increasingly important role in achieving economic development while alleviating environmental pressure. Therefore, this paper selects the A-share renewable energy listed companies in China between 2014 and 2019 as samples, using the fixed-effect model and the logit model to explore the effect of technology innovation on corporate sustainability. We find that technology innovation has a positive effect on both financial sustainability (FS) and social and environmental sustainability (SES). Due to the imbalance of regional social and environmental development and different degrees of emphasis placed on environmental and social responsibility, the positive impact of technology innovation on SES is heterogeneous between the east and the central and west regions. Moreover, as the strategic emerging industry, although the renewable energy industry is granted lots of subsidies from the government, the results show that when government subsidies exceed the threshold, the effect of technology innovation on FS is weakened. Government subsidies have a negative moderating effect on the relationship between innovation and SES. Furthermore, we subdivide government subsidies into government subsidies beforehand (GSB) and government subsidies afterwards (GSA). We reveal that the threshold effect of government subsidies mainly comes from GSA, while the moderating effect of government subsidies is caused by GSA and GSB. This paper is an expansion and enrichment of current studies on sustainable development and also puts forward feasible suggestions for the government to formulate precise and effective subsidy policies to stimulate technology innovation.